Linking Traditional Teaching to Innovative Approaches: Student Conceptions in Kinematics - Ozden Sengul (MDPI AG, 2024)
This study delves into the problem-solving approaches of students who attend classes with traditional teaching methods in university physics education with innovative curriculum materials. This research, conducted with university physics and engineering students, focused on applying research-based curriculum materials in solving kinematic problems. The study analyzes the impact of student knowledge and the distinction between rote learning and scientific practices on conceptual understanding. Student responses are categorized based on the depth of knowledge demonstrated, the skill type utilized, and the degree to which responses indicate a logical progression. These, together with demographic data, are analyzed to determine any patterns. Findings reveal that students use intuitive and mathematical skills to solve a graphical question. However, students employ qualitative and mathematical skill types when they are required to design an experiment. Notably, gender disparity appears to influence the approach to graphical questions, but the design-based question shows no significant relationship between males and females. Gender was likely to contribute to knowledge and logical progression levels, but grades might not show a positive relationship with knowledge level. This study aims to contribute to developing physics education at the university level by highlighting the gap between innovative course materials and their enactment.